The ASEAN Regional Forum - Severino, Rodolfo (Institute of Southeast Asian Studies, 2009)
The ASEAN Regional Forum (ARF) is the only Asia-Pacific-wide forum for consultations and dialogue on political and security issues. Although many articles and books have been published on the ARF, this is one of the few books that treat the forum comprehensively and from the standpoint of the region itself. It traces the ARF's origins, the efforts to move it from confidence building to "preventive diplomacy", and the forces that hold them back, analysing the strategic environment that both constrains the ARF and makes it essential. The book discusses the question of participation, describes the numerous cooperative activities that the participants undertake, and deals with the issue of institutionalization. Finally, it assesses the ARF as a forum and a process on its own terms. The book is written by the former ASEAN Secretary-General and former senior official who was involved in the ARF's early years